Pengaruh Green Marketing Terhadap Keputusan Pembelian Konsumen Kentucky Fried Chicken (KFC) Bandung Timur - Syahla An’nas Tasya; Helin Garlinia Yudawisastra (Jurnal Ilmiah Literasi Indonesia, 2025)
The growing public awareness of environmental issues has encouraged companies to implement environmentally friendly marketing strategies known as green marketing. This study aims to analyze the influence of green marketing on consumer behavior at KFC fast food restaurants. A quantitative research approach was employed, with data collected through questionnaires distributed to KFC consumers. The collected data were analyzed using statistical methods to examine the relationship between green marketing and consumer behavior. The results indicate that green marketing has a positive and significant effect on KFC consumer behavior. Environmentally friendly programs, the use of sustainable packaging, and effective environmental communication contribute to positive consumer attitudes, purchase intentions, and customer loyalty. Therefore, green marketing can be considered an effective strategy for KFC in building a sustainable brand image and encouraging environmentally conscious consumer behavior.